2020
DOI: 10.1111/and.13608
|View full text |Cite
|
Sign up to set email alerts
|

High levels of oxidation–reduction potential in frozen‐thawed human semen are significantly correlated with poor post‐thaw sperm quality

Abstract: This study examined the relationship between oxidation–reduction potential (ORP) in frozen‐thawed semen and the post‐thaw sperm parameters. Levels of ORP were measured in 25 samples from men presenting for routine infertility work‐up and were expressed as millivolt (mV)/106 sperm/ml. Frozen‐thawed samples were examined for post‐thaw total motility (TM%), progressive motility (PM%), total sperm count (TSC) and ORP. The cryo‐survival rate (CSR) was calculated as post‐thaw TM/pre‐freeze TM × 100. Data are provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…ROS are very short-lived, and levels do not remain stable in semen over time (Vessey et al, 2014) published observations for the reliability of measuring sORP in fresh versus frozen semen samples Agarwal, Parekh, et al, 2019;Agarwal et al, 2016), this is the first time that the data and statistical analysis has been reported for snap freezing of raw semen to confirm this observation. Interestingly, a recent paper by Saleh et al (2020) has reported a significant increase in sORP in frozen-thawed semen frozen in cryoprotectant, which confirms previous observations by Thomson et al (2009) that the cryopreservation process induces seminal oxidative stress. The difference in observations between snap freezing raw semen versus freezing in cryoprotectant may be due in part to the length of time that the sperm are exposed to cryoprotectant before freezing and in the absence of antioxidant supplementation.…”
Section: Discussionsupporting
confidence: 82%
“…ROS are very short-lived, and levels do not remain stable in semen over time (Vessey et al, 2014) published observations for the reliability of measuring sORP in fresh versus frozen semen samples Agarwal, Parekh, et al, 2019;Agarwal et al, 2016), this is the first time that the data and statistical analysis has been reported for snap freezing of raw semen to confirm this observation. Interestingly, a recent paper by Saleh et al (2020) has reported a significant increase in sORP in frozen-thawed semen frozen in cryoprotectant, which confirms previous observations by Thomson et al (2009) that the cryopreservation process induces seminal oxidative stress. The difference in observations between snap freezing raw semen versus freezing in cryoprotectant may be due in part to the length of time that the sperm are exposed to cryoprotectant before freezing and in the absence of antioxidant supplementation.…”
Section: Discussionsupporting
confidence: 82%
“…Many studies showed a significant differences in semen components according ram age, many of these differences because of changes in DNA structure [9]. Another studies proved a huge changes in semen components such as ROS , SOD and GPX enzymes levels which lead to crucial changes and wide variation in semen efficiency or ability for fertilization [10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…This fact could be explained by the sensibility of MiOXSYS ® . In our previous studies, MiOXSYS ® technology has usually been employed to compare ram sperm with a highly different level of damage and oxidative stress: fresh, cooled and thawed samples that trigger a redox imbalance reflected in MiOXSYS ® indexes [ 53 , 55 ]. In this study, all samples were cryopreserved, and the great cryopreservation effect on redox balance could mask the differences among our experimental conditions (different frequency of semen collection).…”
Section: Discussionmentioning
confidence: 99%